Distance Learning Strategies at SD Muhammadiyah 1 Krian During the Covid-19 Pandemic - Dyaz Ramadhani Novitasari; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The purpose of this study was to describe the strategy for implementing online learning during the Covid-19 pandemic at SD Muhammadiyah 1 Krian. This study uses a descriptive qualitative approach. Is one of the types of research that is included in the type of qualitative research. The purpose of this research is to reveal events or facts, circumstances, phenomena, variables and circumstances that occurred during the research by presenting what actually happened. This study interprets and describes data related to the current situation, attitudes and views that occur in a society, the conflict between two or more circumstances, the relationship between variables that arise, the differences between existing facts and their influence on a condition, and so on. . In this study, it explains how the strategy carried out by SD Muhammadiyah 1 Krian is when the pandemic is still high, learning in schools uses online and if the pandemic has decreased, the school plans to do offline learning at school but also must always obey health regulations. But the fact is that at SD Muhammadiyah 1 Krian still uses the online system, even though there is an appeal from the government to be able to do offline learning, but for one reason or another, many parents do not agree if learning is done offline. Data collection techniques used include interviews and observations. The results of this study indicate that the strategy for implementing learning during the covid-19 pandemic is what media are used to deal with distance learning that makes students not feel bored quickly.